Azole-synergistic anti-candidal activity of altenusin, a biphenyl metabolite of the endophytic fungus Alternaria alternata isolated from Terminalia chebula Retz. - Jatuporn Phaopongthai (2018)
In this study, a tropical endophytic fungus, Alternaria alternata Tche-153 was isolated from a Thai medicinal plant Terminalia chebula Rezt. The ethyl acetate extract prepared from the fermentation broth exhibited significant ketoconazole-synergistic activity against Candida albicans. Bioassay-directed fractionation of the ethyl acetate extract led to the isolation of altenusin (1), isoochracinic acid (2), and altenuic acid (3) together with 2,5-dimethyl-7-hydroxychromone (4). Using the disc diffusion method and the microdilution chequerboard technique, only altenusin (1) in combination with each of three azole drugs, ketoconazole, fluconazole or itraconazole at their low sub-inhibitory concentrations exhibited potent synergistic activity against C. albicans with the fractional inhibitory concentration index range of 0.078 to 0.188. This first discovery of altenusin (1) as a new azole-synergistic prototype possessing a biphenyl structure is of significance for further development of new azole-synergists to treat invasive candidiasis. © 2013 The Microbiological Society of Korea and Springer-Verlag Berlin Heidelberg.